LOGICAL AND ANALYTICAL TEACHING METHODS FOR THE FORMATION OF LINGUISTIC PERSONALITY IN FOREIGN MEDICAL STUDENTS AT THE RUSSIAN LANGUAGE CLASSES (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-142-148The aim of his article is to consider the problems of formation of linguistic (speech) personality of international students learning the subjects of a medical University in the intermediary language who in the future will be able to comprehend adequately theoretical and practical educational material of medical science when working with patients during training practice in hospitals and clinics.The use of logical and analytical methods of teaching at the Russian language classes is effective.They develop logic, thinking, ability of analyze and synthesize learning material.Key words: foreign medical students, intermediary language, formation of the linguistic personality, Russian as a foreign language, logical and analytical methods of teaching